Character Revitalization through Islamic Religious Education in Schools - Kholidah Nur; Ali Masran Daulay; Junita Irawati (Schemata: Jurnal Pascasarjana UIN Mataram, 2025)
The Indonesian nation is a nation that has various races and cultures. This diversity makes it a nation that has its own character that is different from other nations. This character should be maintained through educational institutions in order to produce a generation of the nation that knows and preserves the character of the nation that has existed since their ancestors. This study uses a qualitative approach with a post-positivistic paradigm. Data collection through interviews, observations, and documentation. While data analysis with the Miles Huberman model. This study resulted in a shift in the character of the Indonesian nation that is classified as very complicated, this complexity is further complicated by the lack of public awareness that our national character has long been lost. The glittering currents of modernization and globalization are the main factors in the loss of the nation's character. The readiness of society to face the modern era forces them to fall asleep and be lulled by the strains of electronic sophistication without being able to fortify themselves with sufficient knowledge. Likewise, the sudden flow of globalization cannot be blocked by clarity of heart and mind so that it blinds the paradigm of long-term thinking. As a result, the character of the nation is now just a sweet memory when remembered and bitter when remembered. The development of national character in schools through Islamic religious education is carried out in several stages, namely familiarizing oneself with religious activities, action planning and giving awards.